Development of a block-modular method for the preparation of monomethinecyanines - E. A. Gorkina; A. Yu. Nikolayev; A. Yu. Gervald; S. K. Sazonov; E. Yu. Bulychev (Тонкие химические технологии, 2013)
A block-modular synthesis of thiamonomethine dyes – effective photosensitizers – was explored. For the first time the method of differential scanning calorimetry was applied to determine the thermophysical characteristics of monomethinecyanine dyes.